The role of the United Nations in Rwandan genocide - Straume, Viktorija (Riga Graduate School of Law, 2019)
This paper concerns the genocide that happened in Rwanda in 1994, where almost 800,000 people were brutally killed. The aim of this paper is to examine why such organization such as the United Nations, which main purpose is to maintain peace and security, failed to prevent genocide and did not take all the necessary measure in order to stop massive massacres in the territory of Rwanda. The paper will analyze how the United Nations and its Member States is responsible for the killings that happened in Rwanda during the 100 days and why it was not prevented
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; United Nations